2006
DOI: 10.5194/nhess-6-597-2006
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal precipitation error propagation in runoff modelling: a case study in central Sweden

Abstract: Abstract. The propagation of spatio-temporal errors in precipitation estimates to runoff errors in the output from the conceptual hydrological HBV model was investigated. The study region was the Gimån catchment in central Sweden, and the period year 2002. Five precipitation sources were considered: NWP model (H22), weather radar (RAD), precipitation gauges (PTH), and two versions of a mesoscale analysis system (M11, M22). To define the baseline estimates of precipitation and runoff, used to define seasonal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The following seasonal classification was used: winter (January, February, March); spring (April, May, June); summer (July, August, September); and autumn (October, November, December). This seasonal classification has been used in other Swedish hydrologic studies [e.g., Olsson , ] and captures variability in the annual hydrologic regime (winter: low flow and typically ice covered, spring: high flow snowmelt, summer and autumn: low flows with high flow events associated with rain events), as well as differences in plant productivity, particularly between the summer and autumn periods [ Peichl et al , ]. For each year and season we calculated carbon export and mean flow‐weighted concentrations of TOC, DIC and CH 4 ‐C.…”
Section: Methodsmentioning
confidence: 99%
“…The following seasonal classification was used: winter (January, February, March); spring (April, May, June); summer (July, August, September); and autumn (October, November, December). This seasonal classification has been used in other Swedish hydrologic studies [e.g., Olsson , ] and captures variability in the annual hydrologic regime (winter: low flow and typically ice covered, spring: high flow snowmelt, summer and autumn: low flows with high flow events associated with rain events), as well as differences in plant productivity, particularly between the summer and autumn periods [ Peichl et al , ]. For each year and season we calculated carbon export and mean flow‐weighted concentrations of TOC, DIC and CH 4 ‐C.…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that the magnitude of errors in runoff (volume and peak) are nearly double that of rainfall volume errors for a 21.2-km 2 catchment, runoff errors amplifying as the total rainfall volume became smaller. Olsson (2006) considered five rainfall sources and used one as the true source, its associated runoff generated by a rainfall-runoff model also considered the true runoff. He observed discharge bias of up to 79% for catchments ranging between 134 and 2133 km 2 using a 1-day simulation timescale.…”
Section: Introductionmentioning
confidence: 99%